Poetic Storytelling in Contemporary Photography. Relation to Nature and the Poesis of Everyday Life in Works of Selected Artist in Iceland and Other Nordic Countries - Sigrún Alba Sigurðardóttir (Arts, 2020)
The past 20 years have seen a shift in Icelandic photography from postmodern aesthetics towards a more phenomenological perspective that explores the relationship between subjective and affective truth on the one hand, and the outside world on the other hand. Rather than telling a story about the world as it is or as the photographer wants it to appear, the focus is on communicating with the world, and with the viewer. The photograph is seen as a creative medium that can be used to reflect how we experience and make sense of the world, or how we are and dwell in the world. In this paper, I introduce the theme of poetic storytelling in the context of contemporary photography in Iceland and other Nordic Countries. Poetic storytelling is a term I have been developing to describe a certain lyrical way to use a photograph as a narrative medium in reaction to the climate crisis and to a general lack of relation to oneself and to the world in times of increased acceleration in the society. In my article I analyze works by a few leading Icelandic photographers (Katrín Elvarsdóttir, Heiða Helgadóttir and Hallgerður Hallgrímsdóttir) and put them in context with works by artists from Denmark (Joakim Eskildsen, Christina Capetillo and Astrid Kruse Jensen), Sweden (Helene Schmitz) and Finland (Hertta Kiiski) artists within the frame of poetic storytelling. Poetic storytelling is about a way to use a photograph as a narrative medium in an attempt to grasp a reality which is neither fully objective nor subjective, but rather a bit of both.